Dziennik bpa Mikołaja Sasinowskiego (część 1) - Guzewicz, Wojciech (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
The first part of Bishop Mikołaj Sasinowski's wartime diary covers the period from September 1 to September 17, 1939. The whole thing was typewritten on 107 sheets of A4 paper. Many of the cards show damage caused by the passage of time as well as by human activity – most of them by Bishop Edward Samsel (e.g. additions, deletions, joining texts, etc.). The value of memories is that they were written by an eyewitness and an active creator of the then ecclesiastical and political reality. They are also a great source of knowledge about the history of Poles in exile during World War II. Finally, they enrich our knowledge of the religious and social life of the author himse.